Impact of cancer on everyday life: a systematic appraisal of the research evidence - Okamoto, Ikumi (Health Expect, 2011)
Objective  To conduct a systematic appraisal of the published literature reviews related to the impact of cancer on everyday life. This theme was identified as the top priority area for research by participants in the Macmillan Listening Study, which was the first UK‐wide public consultation exercise to identify patients’ priorities for cancer research. Search strategy  The top priority area was divided into ten sub‐themes, and a modified systematic review was undertaken for each sub‐theme using electronic searches. Inclusion criteria  Literature review papers were included if they were written in English, involved patients diagnosed ≥18 years, any cancer types and published between 2000 and 2006. Data extraction and synthesis  Two thousand and two hundred and fifty‐two potentially eligible papers were identified. Abstracts were read by the first author and selected for inclusion in the review. Twenty percentages of the papers were also read independently by other authors. Sixty‐two review papers were finally selected. Main results  The systematic appraisal revealed that some sub‐themes of the patient‐identified priority area (e.g., how to support family members of cancer patients) were under‐researched, while other sub‐themes (e.g., anxiety and depression experienced by cancer patients) had been explored to some extent. Certain areas of research interest to patients were found to have been explored; however, their significance was limited by the quality of the research. Conclusion  The systematic appraisal highlights important areas for future research and the need for more effective dissemination of study findings to wider audiences, including service users. This study also indicates the need for further research to enhance the generalizability and/or significance of findings.